'The Returned Pilgrim': Nancy Astor and Plymouth. Issue 1 (26th February 2021) - Rowbotham, Judith
This article focuses on the evolution of Nancy Astor's political persona, dating it back to 1908 when she first visited Plymouth when her husband Waldorf Astor was being considered as the junior Unionist candidate for the borough. It reveals how, by 1919 when she was elected, she had already formed the political ideas and identified the key campaigning issues that she would pursue between 1919 and 1945, as a result of her experiences at Plymouth. It argues that Plymouth is a key factor to understanding Nancy Astor's political identity and expressions of her view, and that the foundation created for these between 1908 and 1919 continued to support her further political development after her election for Plymouth Sutton in 1919. The article thus gives insights into an aspect of Nancy Astor's development as 'an unconventional MP' which has hitherto remained largely unfamiliar to those with an interest in her career and work. It reveals a sustained consistency of engagement with a range of issues relating primarily to women's and children's concerns (education, welfare, health, support for employment and training, as well as temperance and promotion of women's political participation) that were shaped by her involvement with these issues in the microcosm provided by Plymouth.